Analisis Dan Perancangan Sistem Informasi Antrian Pasien Pada Praktek Dokter Bersama Oral Healh Centre Berbasis Android Dan Sms Gateway - Hanafi, Muhammad Iqbal; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2021)
Abstract At the location of General Practitioner services we often see many patients queuing for treatment. It is not efficient due to the time that they could use to break or other activities discharged to wait. From these problems, we need a technology to facilitate patient in doing the queue. In this paper designed an online queue of applications that the user is divided into two sides of the patients who did queue using Android-based applications and SMS Gateway and on the Web-based officers. The output of this application is to make the system queue queue process can be done online via android smartphone and also provided a notification feature so that when a queue number that is closest called the patients received a reminder in the form of a notification on android or SMS to the SMS Gateway to soon be able to return to the location of the doctor.